Analisis Jumlah Wisatawan Nusantara, Jumlah Wisatawan Mancanegara, Tingkat Hunian Hotel dan Jumlah Restoran terhadap Pendapatan Asli Daerah di Kabupaten Magelang - Diella Arinta; Niniek Imaningsih (Journal of Management and Bussines (JOMB), 2024)
This research aims to analyze the influence of the number of domestic tourists, the number of foreign tourists, hotel occupancy rates, and the number of restaurants on local revenue in Magelang Regency. The research method used is multiple linear regression using the Eviews 12 program, using data from the Central Statistics Agency of Magelang Regency and BPS Central Java from 2008 to 2021. The results of the research show that the number of domestic tourists, the number of foreign tourists, and the hotel occupancy rate are not has a significant influence on local revenue, while the number of restaurants has a significant influence on local revenue in Magelang Regency. In conclusion, the important role of restaurants in increasing regional income through the tourism sector. Keywords: Number of Indonesian Tourists, Number of Foreign Tourists